2012
DOI: 10.13005/ojc/280317
|View full text |Cite
|
Sign up to set email alerts
|

Silica Supported Zinc (II) Chloride (SiO2-ZnCl2) as an Efficient Catalyst for the Eco-Friendly Synthesis of 2,3-Dihydroquinazolin-4(1H)-Ones

Abstract: Silica supported zinc (II) chloride (SiO 2 -ZnCl 2 ) as an efficient and non-toxic heterogeneous catalyst have been used for the simple and facile synthesis of 2,3-dihydroquinazolin-4(1H)-ones through the direct cyclo-condensation of anthranilamide and aldehydes or one-pot three-component cyclo-condensation of isatoic anhydride, ammonium acetate (or amines) and aldehydes under solvent-free conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…A persual of available literature shows that systemic study on complexation of zinc with sulphonyl ureas is relatively scanty. [7][8][9][10] The study of chemistry and chemical reaction of structure co-ordination compound helps in establishing structure activity relationship. It has been reported that in biological activity metal complex is more potent and less toxic as compared to the free ligand 11 .…”
mentioning
confidence: 99%
“…A persual of available literature shows that systemic study on complexation of zinc with sulphonyl ureas is relatively scanty. [7][8][9][10] The study of chemistry and chemical reaction of structure co-ordination compound helps in establishing structure activity relationship. It has been reported that in biological activity metal complex is more potent and less toxic as compared to the free ligand 11 .…”
mentioning
confidence: 99%
“…In general, the use of heterogeneous and reusable catalysts afforded high yields, up to 99%, in very short times. A number of solid acid catalysts, on various supports, such as silica, [130][131][132][133][134][135][136][137][138] and clay, 139,140 as well as different catalysts bearing sulfonic acid groups and anchored on cellulose, 141 Wang resin, 142 NPs, 143,144 and other supports, 145,146 were employed. Reusable acid-surfactantcombined catalysts, 147,148 and heteropolyacids, 149-152 have also emerged as good catalysts, due to their unique properties like high thermal stability, low cost, ease of preparation and recovery.…”
Section: Heterogeneous/recyclable Catalystsmentioning
confidence: 99%
“…Heterocycles bearing quinazoline core structures played a significant role in research fields such as chemistry, drug development and biological investigations (Ghashang, 2012;Ghashang et al, 2013Ghashang et al, , 2015. Quinazoline and especially quinazoline-2,4(1H,3H)-dione derivatives have attracted significant attention due to diverse pharmacological activities such as anti-proliferative activities against HCT-116 and MCF-7 cell lines (Hei et al, 2016), anti-proliferative activity in LNCaP and prostate cancer cell lines (Maestri et al, 2017), isoform-selective PI3K-α inhibition (Yadav et al, 2016), PARP-1/2 inhibition activity (Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%